2016
DOI: 10.1039/c6ra08031f
|View full text |Cite
|
Sign up to set email alerts
|

Highly repeatable kinetically-independent synthesis of one- and two-dimensional silver nanostructures by oriented attachment

Abstract: A repeatable and fast synthesis of one- and two-dimensional silver nanostructures with thickness of 20–25 nm, constructed from highly stable hexagonal and triangular nanoplates has been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…During the reduction process, Ag + can be complexed with PMAA first instead of being reduced by VC 53 because normally VC cannot easily reduce Ag + at room temperature unless external heat 54 or other metastable silver ions (e.g., ammonium silver complex) 55 are supplied. Since there is no electron transfer that occurs during the formation of the PMAA-Ag complex, while the redox reaction with electron transfer will happen only after the redox potential reaching the threshold, 56 ion exchange would take precedence over the redox reaction to form the PMAA-Ag complex in the mixed solution. This reduction process is illustrated in Figure 6a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…During the reduction process, Ag + can be complexed with PMAA first instead of being reduced by VC 53 because normally VC cannot easily reduce Ag + at room temperature unless external heat 54 or other metastable silver ions (e.g., ammonium silver complex) 55 are supplied. Since there is no electron transfer that occurs during the formation of the PMAA-Ag complex, while the redox reaction with electron transfer will happen only after the redox potential reaching the threshold, 56 ion exchange would take precedence over the redox reaction to form the PMAA-Ag complex in the mixed solution. This reduction process is illustrated in Figure 6a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…74 In particular, recent studies showed that shape-anisotropic van der Waals interactions play an important role in the growth of 1D and 2D structures via OA. [75][76][77][78][79] Other examples of OA driven by macroscopic interactions include particle-based growth of CdTe nanowires, which is thought to be driven by macroscopic dipole-dipole interparticle interactions. 80 We note that although ligands were used in that work as surface stabilizing agents for CdTe nanoparticles they were not considered to contribute to facet selectivity and alignment and their controlled removal was a necessary step for oriented attachment.…”
Section: Discussionmentioning
confidence: 99%
“…The term 'oriented attachment' has been used in recent years to describe the growth mechanism of various anisotropic nanostructures, particularly one dimensional (1D) nanorods/nanowires and two dimensional (2D) nanosheets. [26][27][28][29] The growth kinetics was reported to be extremely sensitive to chemical environments around the nanocrystals which typically include the surfactants present, solvent molecules and ions on the surface. 26 Among these, the surfactants play a crucial role since their specific absorption on certain facets of the crystalline nanoparticle not only leads to generation of anisotropic electrostatic dipolar interactions, but also creates steric hindrancethereby strongly affecting the growth rate and the corresponding energy barrier.…”
Section: Crystengcomm Papermentioning
confidence: 99%